Asymmetric Perception of Gains versus Non‐losses and Losses versus Non‐gains: The Causal Role of Regulatory Focus. (26th April 2013) - Sacchi, Simona; Stanca, Luca
ABSTRACT Recent studies show that, while losses loom larger than equivalent non‐gains, gains loom larger than equivalent non‐losses. This finding has been interpreted within the framework of regulatory focus theory. In this study, we highlight the importance of considering the motivational focus independently of the framing and the valence of outcome, thus exploring the causal effect of regulatory focus on the asymmetric perception of gains versus non‐losses and losses versus non‐gains. In two studies, we examine the perceived effects of either actual or hypothetical changes in monetary wealth, while orthogonally manipulating framing, valence, and regulatory focus. We find a significant interaction between the three factors. The gain versus non‐loss asymmetry in perceived satisfaction is stronger in promotion focus, whereas the loss versus non‐gain asymmetry in perceived dissatisfaction is stronger in prevention focus. The results suggest that the effects of incentives framed in terms of (non)gains and (non)losses depend on their congruence with the individual's motivational state. Copyright © 2013 John Wiley & Sons, Ltd.